Academic library impact : improving practice and essential areas to research - Connaway, Lynn Silipigni; Harvey, William (Software engineer); Kitzie, Vanessa; Mikitish, Stephanie (Association of College & Research Libraries, a division of the American Library Association, 2017)
Investigates how libraries can increase student learning and success and effectively communicate their value to higher education stakeholders.